Self‐regulation of ventromedial prefrontal cortex activation using real‐time fMRI neurofeedback—Influence of default mode network. Issue 2 (21st October 2019) - Mayeli, Ahmad; Misaki, Masaya; Zotev, Vadim; Tsuchiyagaito, Aki; Al Zoubi, Obada; Phillips, Raquel; Smith, Jared; Stewart, Jennifer L.; Refai, Hazem; Paulus, Martin P.; Bodurka, Jerzy
Abstract: The ventromedial prefrontal cortex (vmPFC) is involved in regulation of negative emotion and decision‐making, emotional and behavioral control, and active resilient coping. This pilot study examined the feasibility of training healthy subjects ( n = 27) to self‐regulate the vmPFC activity using a real‐time functional magnetic resonance imaging neurofeedback (rtfMRI‐nf). Participants in the experimental group (EG, n = 18) were provided with an ongoing vmPFC hemodynamic activity (rtfMRI‐nf signal represented as variable‐height bar). Individuals were instructed to raise the bar by self‐relevant value‐based thinking. Participants in the control group (CG, n = 9) performed the same task; however, they were provided with computer‐generated sham neurofeedback signal. Results demonstrate that (a) both the CG and the EG show a higher vmPFC fMRI signal at the baseline than during neurofeedback training; (b) no significant positive training effect was seen in the vmPFC across neurofeedback runs; however, the medial prefrontal cortex, middle temporal gyri, inferior frontal gyri, and precuneus showed significant decreasing trends across the training runs only for the EG; (c) the vmPFC rtfMRI‐nf signal associated with the fMRI signal across the default mode network (DMN). These findings suggest that it may be difficult to modulate a single DMN region without affecting other DMN regions. Observed decreased vmPFC activity during the neurofeedback task could be due to interference from the fMRI signal within other DMN network regions, as well as interaction with task‐positive networks. Even though participants in the EG did not show significant positive increase in the vmPFC activity among neurofeedback runs, they were able to learn to accommodate the demand of self‐regulation task to maintain the vmPFC activity with the help of a neurofeedback signal.